Real-time impact damage sensing and localization in composites through embedded aligned carbon nanotube sheets. (1st April 2019) - Aly, Karim; Bradford, Philip D.
Abstract: Carbon nanotubes (CNTs) have shown potential as a good candidate for performing strain and damage sensing in composites, however, the number of studies that have examined CNTs piezoresistive response under impact is limited. This paper investigates a novel technique for real-time damage sensing during and after impact strikes on composite laminates. In this technique, aligned CNT sheets layers are distributed through the thickness to monitor the developing damage in the host structure's impact side, mid-plane and non-impact side. This is accomplished through measuring the CNT sheets' in-plane electrical resistance changes simultaneously and linking them to the impact damage modes in the structure. The experimental results demonstrate the CNT layers' ability to detect, locate and quantify impact damage when the host structure undergoes different types of impacts. The results highlight the CNT sensing layers high sensitivity to damage accumulation. Graphical abstract: Image 1